Analysis and design of high gain DC-DC converter for renewable energy applications. (3rd July 2023) - Gnanavadivel, J.; Jayanthi, K.; Vasundhara, S.; Swetha, K.V.; Jeya Keerthana, K.
ABSTRACT: The paper proposes an efficient DC-DC converter for renewable energy applications. The proposed high-gain converter is designed with switched inductor cell and voltage multiplier cell. In the proposed converter, the continuous source current is obtained by switched inductor cells, and high-voltage gain is achieved using voltage multiplier cells. The proposed converter provides a voltage gain of 10 when operated with a duty ratio of 27.3%, whereas a voltage gain of 39 is obtained for an 80% duty ratio. The efficiency of 96.54% is achieved in simulation for the rated condition of 24 V/240 V, 120W. The converter operation under steady-state, state-space modelling, and voltage and current stress of the power semiconductor components are analyzed. In addition to that, loss distribution and efficiency analysis are made. The performance of the converter is analyzed using the Matlab Simulink tool. Also, the experimental hardware prototype model is developed to validate the simulated and theoretical analysis.